Low-Temperature Electron Beam-Induced Transformations of Cesium Lead Halide Perovskite Nanocrystals - Dang, Zhiya (ACS Omega, 2017)
[Image: see text] Cesium lead halide perovskite (CsPbX(3), with X = Br, Cl, I) nanocrystals have been found to undergo severe modifications under the high-energy electron beam irradiation of a transmission electron microscope (80/200 keV). In particular, in our previous work, together with halogen desorption, Pb(2+) ions were found to be reduced to Pb(0) and then diffused to form lead nanoparticles at temperatures above −40 °C. Here, we present a detailed irradiation study of CsPbBr(3) nanocrystals at temperatures below −40 °C, a range in which the diffusion of Pb(0) atoms/clusters is drastically suppressed. Under these conditions, the irradiation instead induces the nucleation of randomly oriented CsBr, CsPb, and PbBr(2) crystalline domains. In addition to the Br desorption, which accompanies Pb(2+) reduction at all the temperatures, Br is also desorbed from the CsBr and PbBr(2) domains at low temperatures, leading to a more pronounced Br loss, thus the final products are mainly composed of Cs and Pb. The overall transformation involves the creation of voids, which coalesce upon further exposure, as demonstrated in both nanosheets and nanocuboids. Our results show that although low temperatures hinder the formation of Pb nanoparticles in CsPbBr(3) nanocrystals when irradiated, the nanocrystals are nevertheless unstable. Consequently, we suggest that an optimum combination of temperature range, electron energy, and dose rate needs to be carefully chosen for the characterization of halide perovskite nanocrystals to minimize both the Pb nanoparticle formation and the structural decomposition.